The Hermeneutic Positioning of the Translator in Quran Translation - Elass, Hicham; Bennoudi, Hanan (International Journal of Language and Literary Studies, 2023)
The transition from the text to the figure of the translator has been a substantial paradigm shift in Translation Studies amidst the cultural and sociological turns of the present context. Not only does current research shift the focus towards studying translation as a socially and ideologically situated activity, governed by various sociocultural and cognitive factors, but it also emphasizes the translator’s role as an active agent of change—an activist. This article explores the hermeneutic positioning of the translator in the realm of Quran translation, aiming to retrieve the active role of the translator from the shackles of the dominant Western models of sacred translation and the exegetical tradition in which the practice of Quran translation is deeply entrenched. The study emanates from the premise that the practice of Quran translation lacks a consistent approach that strikes a balance between the Quran along with its interrelated systems of exegetical authority and the vital position of the translator, as an exegetical interpreter, in the hermeneutic process of translating the Quran. Inspired by Mohammed Abed Al-Jabri’s Quranic hermeneutics, the study advances a middle-way translational approach to Quran translation that spares the confusion and contradictions surrounding the legitimation of the Quran’s interpretation/translation, the significations of exegetical translation (tarjama tafs?riyya), and the problematic embrace of the mainstream Western definition of translation and its inherent negative bearings on the role of the Quran translator. Thus, the article posits that the retrieval of the translator’s central hermeneutic positioning not only hinges on rethinking the translation as/and interpretation of the Quran but also on disconnecting the practice of Quran translation from the Western models of sacred translation to make room for special consideration of the hermeneutic implications of the Arabic term tarjama (translation) as it was practiced in early Islamic history as a form of tafs?r (exegesis) and/or ta’w?l (interpretation) in reference to the sacred text.